2019
DOI: 10.1177/2325967119s00004
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid (Dha) for the Treatment of Pediatric Sport-Related Concussion: Results of a Feasibility Trial

Abstract: Introduction: The rate of sport-related concussion (SRC) has increased steadily over the past two decades in the pediatric population. Docosahexaenoic acid (DHA), an Omega-3 fatty acid important for brain development in children, may aid in recovery following SRC. The purpose of this study was to determine the feasibility, outcomes, and safety of DHA as early treatment for SRC in pediatrics. Methods: A double-blind, randomized, placebo-controlled feasibility trial was conducted. Inclusion criteria were ages 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In addition, specific nutritional supplements and infusions administered during the acute period post mTBI onset may have a role in facilitating patients' recovery. In the present review intakes of nutrients and non-nutrients, including omega-3s fatty acids DHA and EPA (55,58,61), vitamin D (62), magnesium oxide (56), NAC (5), HSL (59), and nootropic cerebrolysin (60) demonstrated a positive effect on recovery outcomes for patients post mTBI. However, due to the diversity between interventions and the limited number of studies conducted in humans, a meta-analysis was not possible.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…In addition, specific nutritional supplements and infusions administered during the acute period post mTBI onset may have a role in facilitating patients' recovery. In the present review intakes of nutrients and non-nutrients, including omega-3s fatty acids DHA and EPA (55,58,61), vitamin D (62), magnesium oxide (56), NAC (5), HSL (59), and nootropic cerebrolysin (60) demonstrated a positive effect on recovery outcomes for patients post mTBI. However, due to the diversity between interventions and the limited number of studies conducted in humans, a meta-analysis was not possible.…”
Section: Discussionmentioning
confidence: 91%
“…Included studies reported a diverse range of recovery measures and outcomes for patients during acute recovery periods 0-14 days for adults and 0-28 days for children post mTBI onset (8,66). Nine out of the 11 included studies reported positive recovery outcomes utilizing nutritional interventions in those that sustained an mTBI (5, 55,56,[58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations